3D Assessment of Nasolabial Appearance in Patients With Complete Unilateral Cleft Lip and Palate. (February 2018) - Bagante, Ieva; Zepa, Inta; Akota, Ilze
Objective: Rhinoplasty in patients with complete unilateral cleft lip and palate (UCLP) is challenging, and the surgical outcome of the nose is complicated to evaluate. The aim of this study was to assess the nasolabial appearance of patients with UCLP compared with a control group. Design: Cross-sectional study. Setting: Riga Cleft Lip and Palate Centre, Latvia. Participants: All consecutive 35 patients born between 1994 and 2004 with nonsyndromic complete UCLP were included. Of 35 patients, 29 came for checkup; the mean age was 14.7 years (range 10-18). In the control group, 35 noncleft participants at 10 years of age were included. Interventions: Nasolabial appearance was evaluated from 3-dimensional images using a 3-dimensional stereo-photogrammetric camera setup (3dMDface System), the results being analysed statistically. Results: In UCLP group, a statistically significant difference between cleft and noncleft side was found only in alar wing length ( P < .05). The difference of nasolabial anthropometric distances in the control group between the left and right side was not significant. The difference between the UCLP group and the control group was significant in all anthropometric distances except the lateral lip length to cupid's bow. Conclusions: The nasolabial appearance with acceptable symmetry after cleft lip and reconstructive surgery of the nose was achieved. Symmetry of the nasolabial appearance in patients with UCLP differed from those in the control group. The 3D photographs with a proposed set of anthropometric landmarks for evaluation of nasolabial appearance seems to be a convenient, accurate, and noninvasive way to follow and evaluate patients after surgery.